Identification and Classification of Rare Variants in NPC1 and NPC2 in Quebec - Lahoud Touma (Nature Portfolio, 2021)
Abstract Niemann–Pick disease type C (NPC) is a treatable autosomal recessive neurodegenerative condition which leads to a variety of progressive manifestations. Despite most cases being diagnosed at a young age, disease prevalence may be underestimated, especially in adults, and interpretation of NPC1 and NPC2 variants can be difficult. This study aims to identify potential pathogenic variants in a large cohort of healthy individuals and classify their risk of pathogenicity to assist with future interpretation of variants. The CARTaGENE (CaG) cohort was used to identify possible variants of NPC1 and NPC2. Nine-hundred and eleven RNA samples and 198 exome sequencing were screened for genetic variants through a bio-informatic pipeline performing alignment and variant calling. The identified variants were analyzed using annotations for allelic frequency, pathogenicity and conservation scores. The ACMG guidelines were used to classify the variants. These were then compared to existing databases and previous studies of NPC prevalence, including the Tübingen NPC database. Thirty-two distinct variants were identified after running the samples in the RNA-sequencing pipeline, two of which were classified as pathogenic and 21 of which were not published previously. Furthermore, 46 variants were both identified in our population and with the Tübingen database, the majority of which were of uncertain significance. Ten additional variants were found in our exome-sequencing sample. This study of a sample from a population living in Quebec demonstrates a variety of rare variants, some of which were already described in the literature as well as some novel variants. Classifying these variants is arduous given the scarcity of available literature, even so in a population of healthy individuals. Yet using this data, we were able to identify two pathogenic variants within our population and several new variants not previously identified.